Simone Piazza, Pittura rupestre medievale. Lazio e Campania settentrionale (secoli VI-XIII) - Maraković, Nikolina (Array, 2008)
The article is a review of a book by S. Piazza, which deals with the painting in the churches in the rocks of Latium and Campania.